Enhanced production of thermophilic xylanase by recombinant Escherichia coli DH5a through optimization of medium and dissolved oxygen level. - Basar, Basilar; Mohamed, Mohd Shamzi; Mohamed, Rosfarizan; Puspaningsih, Ni Nyoman Tri; Ariff, Arbakariya (Friends Science Publishers, 2010)
Enhancement of thermophilic xylanase production by recombinant Escherichia coli DH5α through suitable medium formulation was initially investigated using shake flask cultures. Thereafter the effect of dissolved oxygen tension (DOT) level on the performance of xylanase fermentation by E. coli DH5α was investigated in 2 L stirred tank bioreactor using the optimal medium. Among the two basal medium tested (complex medium of Luria Bertani & defined mineral medium), defined mineral medium gave the highest growth and xylanase production. The optimal glucose and (NH4)2504 for xylanase production was obtained at 10 g L -1 and 2 g L-1, respectively. Growth of E. coli DH5α and xylanase production was inhibited in oxygen limited fermentation, where dissolved oxygen tension level was controlled at 0% saturation. On the other hand,xylanase production was enhanced at DOT level controlled at 20% saturation, though growth was not significantly improved. Substantially high xylanase production (1784.57 U mL -1) was obtained in fermentation using optimal medium composition and DOT level. These results indicate that efficient process control strategy is important for the mass production of xylanase enzyme by E. coli DH5α.